Arbovirus epidemic in the Juan León Mallorquín health center in Paraguay - Villamayor Amarilla, Andrea; Velazquez, Makarena; Guimarães Brito, Raianny; Ferreira Feijão, Mirella Régia; Estevão Ferreira, Hamanda Victória (Salud, Ciencia y Tecnología, 2023)
The term arboviruses was used in the 1930s, when several viruses were isolated from arthropods, with the Aedes aegypti mosquito as the main vector. When infected, mosquitoes infect individuals through the bite, raising concern in relation to the public health context as they cause major epidemics in different parts of the world. Among them, those with greater evidence are Dengue, Zika Virus and Chikungunya. This article aims to identify and analyze the epidemiological profile of arbovirus infections in the city of Doctor Juan León Mallorquín, Paraguay, through the epidemiology sector of the Health Center of Juan León Marlloquín, epidemiological data were made available, using a form epidemiology of Arbovirus and a study of research articles through a bibliographic review. The data were reorganized and referred. We observed that the tendency of cases is to increase gradually, since changes in temperature, food availability and the amount of larvae contribute significantly to the development of the mosquito. In the analysis of the descriptive study and epidemiological profile on the transmission of the arboviruses Dengue, Zika and Chikungunya in this article, it was pointed out that of the 169 cases notified from January 2021 to February 2023, 102 were women, with a higher prevalence in the age group from 1 to 10 years old. The most common symptoms were fever, myalgia, arthralgia and headache. In view of the above, the repercussion that these arboviruses cause is noticeable and how essential their control is. In this sense, it denotes the importance of data collection for new ideas and investments for the creation of health strategies, aimed at controlling the vector of these specific diseases